Magnolol-derived thiol-ene photo-polymerized membranes with intrinsic anti-flammability and high transparency. (1st August 2022) - Guo, Wenwen; Liang, Fuwei; Chen, Shun; Yu, Kejing; Sun, Jie; Pang, Zengyuan; Fei, Bin
Abstract: In this study, a phosphorus-containing bio-based monomer (MBDPP) was first synthesized from renewable magnolol, and subsequently photo-cured with tri-thiol (TPTMP) or tetra-thiol (PETMP) monomers via thiol–ene polymerization. The synthesized MBDPP/TPTMP and MBDPP/PETMP membranes exhibited high char residues at 700 °C in the TGA tests, which were 19.8 wt% and 24.2 wt% for nitrogen while 16.5 wt% and 20.2 wt% for air, respectively, indicating superior charring capacity of both membranes. DMA results indicated that both the higher stiffness and the Tg of the cured MBDPP/PETMP membrane was ascribed to its higher cross-linking density than that of the cured MBDPP/TPTMP owing to the tetra-functional groups of PETMP. In the open flame test, both MBDPP/TPTMP and MBDPP/PETMP membranes self-extinguished immediately when removing the flame source, manifesting excellent intrinsic anti-flammability. The cone calorimeter results further demonstrated that MBDPP/TPTMP and MBDPP/PETMP membranes showed lower PHRR (419 and 388 kW/m 2, respectively) and THR (41.38 and 38.98 MJ/m 2, respectively) values than most of the thiol-ene photo-polymerized counterparts previously reported. The excellent anti-flammability of MBDPP/TPTMP and MBDPP/PETMP membranes originated from the formation of expandable char residues that played an efficient role in hampering the transfer of flammable pyrolysis products to flame zone as well as insulating the heat irradiation during combustion. Additionally, both MBDPP/TPTMP and MBDPP/PETMP membranes showed excellent transparency (transmittance >85% in the visible region) and flexibility (breaking elongation around 40%). Taking the intrinsic anti-flammability, exceptional transparency and high flexibility into account, the MBDPP/TPTMP and MBDPP/PETMP systems are suitable as intumescent flame retardant coating materials. Graphical abstract: Image 1